If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3xy + 3yx = 0 Combine like terms: 3xy + 3xy = 6xy 6xy = 0 Solving 6xy = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '6'. xy = 0 Simplifying xy = 0 The solution to this equation could not be determined.
| mx+25=-36 | | f=73905/15 | | 3xy=3yx | | m+7m-3m+4= | | X^2-8=3 | | 73905=n/15 | | V=3.14R2h/3 | | -3/2(1) | | -2-2w+2=2-7w+2 | | m-2m-8m+7= | | 0=-2x^2+6x | | (2xy)(5xy)= | | 5x+85-53/2x=51 | | 32x^2+12x+1= | | 12y^2(y/3+9x/y2)=4y^3-72 | | 4z-3(z+1)=2(z-3)-z | | 11/6/(-8) | | 49x^2-14x-48= | | -21x^2-31x-8= | | 13=-7x-8 | | -8(x+2)=24 | | 16x^2+34x+15= | | 6(3)-k=48 | | 3xsq-48x= | | (5t-s)(5t-s)= | | 2n+yr=r-7g | | 8-2z=-5-2z | | 41=12x+5 | | 9t-6t+t-2=17t | | 84=-2m-4(-4m+7) | | 7x^2-17x+6= | | Log[3](7)-Log[3](5)= |